Study of scale effect on strength characteristic of stabilised composite with sewage sludge – Part A: Preliminary study - Amiralian, Saeid; Budihardjo, Mochamad Arief; Chegenizadeh, Amin; Nikraz, Hamid (ELSEVIER, 2015)
Nowadays, the sustainable management of wastewater materials is a highly debated issue around the world. In recent years, there has been a tendency to use sewage sludge for agricultural applications. However, there has been limited investigation of the utilisation of sewage sludge for geotechnical applications. Taking into account that the use of large-scale and material characterisation tests has not been properly addressed so far, this research presents a comprehensive study on sewage sludge stabilisation in two parts; part A: a review and preliminary study, and part B: a comprehensive experimental and microanalytical investigation.